The Role of Facebook in Crush the Crave, a Mobile- and Social Media-Based Smoking Cessation Intervention: Qualitative Framework Analysis of Posts - Struik, Laura Louise; Baskerville, Neill Bruce (JMIR Publications, 2014)
BackgroundSocial networking sites, particularly Facebook, are increasingly included in contemporary smoking cessation interventions directed toward young adults. Little is known about the role of Facebook in smoking cessation interventions directed toward this age demographic. ObjectiveThe aim of this study was to characterize the content of posts on the Facebook page of Crush the Crave, an evidence-informed smoking cessation intervention directed toward young adults aged 19 to 29 years. MethodsCrush the Crave Facebook posts between October 10, 2012 and June 12, 2013 were collected for analysis, representing page activity during the pilot phase of Crush the Crave. Of the 399 posts included for analysis, 121 were original posts, whereas the remaining 278 were reply posts. Posts were coded according to themes using framework analysis. ResultsWe found that the original Crush the Crave Facebook posts served two main purposes: to support smoking cessation and to market Crush the Crave. Most of the original posts (86/121, 71.1%) conveyed support of smoking cessation through the following 7 subthemes: encouraging cessation, group stimulation, management of cravings, promoting social support, denormalizing smoking, providing health information, and exposing tobacco industry tactics. The remaining original posts (35/121, 28.9%) aimed to market Crush the Crave through 2 subthemes: Crush the Crave promotion and iPhone 5 contest promotion. Most of the reply posts (214/278, 77.0%) were in response to the supporting smoking cessation posts and the remaining 64 (23.0%) were in response to the marketing Crush the Crave posts. The most common response to both the supporting smoking cessation and marketing Crush the Crave posts was user engagement with the images associated with each post at 40.2% (86/214) and 45% (29/64), respectively. The second most common response consisted of users sharing their smoking-related experiences. More users shared their smoking-related experiences in response to the supporting smoking cessation posts (81/214, 37.9%) compared to the marketing Crush the Crave posts (11/64, 17%). With the exception of 4 posts, a moderator posted all the original posts. In addition, although 56.00% (18,937/33,815) of Crush the Crave Facebook page users were men, only 19.8% (55/278) of the reply posts were made by men. Finally, men were found to be more likely to express sarcasm or make strong assertions about quitting smoking and Crush the Crave than women. ConclusionsThe CTC Facebook page presents as a unique platform for supporting young adult smoking cessation at all stages of the cessation process. The findings of this study indicate that social networking sites, especially Facebook, warrant inclusion in tobacco control efforts directed towards young adults. Research on effectiveness of the Facebook page for quitting smoking is needed.